2006
DOI: 10.1385/endo:29:1:129
|View full text |Cite
|
Sign up to set email alerts
|

The Estrogenic Effect of Pueraria mirifica on Gonadotrophin Levels in Aged Monkeys

Abstract: We investigated the effect of Pueraria mirifica (PM) on gonadotrophin and estradiol levels in aged animals; nine menopausal cynomolgus monkeys were divided into three groups. Each group (n = 3) was fed with 10, 100, and 1000 mg/d of PM for 90 d. PM-10 induced the decrease of follicle stimulating hormone (FSH) levels on d 15-90 in one out of three monkeys. PM-100 and PM-1000 decreased FSH levels of all monkeys throughout the treatment period. After the treatment period, FSH levels continued to decrease for 5 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
78
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 32 publications
7
78
1
Order By: Relevance
“…However, the change in sexual skin coloration w a s n o t c o n c o m i t a n t w i t h t h e c h a n g e i n endogenous estradiol level in serum [10]. Serum estradiol levels were unchanged, but tended to decrease in three monkey groups in a previous study [10].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…However, the change in sexual skin coloration w a s n o t c o n c o m i t a n t w i t h t h e c h a n g e i n endogenous estradiol level in serum [10]. Serum estradiol levels were unchanged, but tended to decrease in three monkey groups in a previous study [10].…”
Section: Discussionmentioning
confidence: 69%
“…Administration of PM produced cornified cells, g r o w t h o f t h e e n d o m e t r i u m g l a n d , a n d proliferation of spiral arteries in ovariectomized rats [9]. Furthermore, we reported in a recent investigation that daily feeding of PM had an estrogenic effect by suppressing gonadotropin and estrogen secretions in aged female cynomolgus monkeys [10].The influence of estrogen on the sexual skin area around the perineum to the base of the tail has been …”
mentioning
confidence: 99%
“…Consumption of the tuberous powder generates a strong estrogenic activity as revealed by the induction of vaginal cornification in ovariectomized rats (5,6) and by the MCF-7 cell proliferation assay (7). Treatment of gonadectomized rats with plant tuber powder resulted in a reduction of LH and FSH levels (8), with dose-dependent estrogenic responses in female mice (9), female monkeys (10), and menopausal monkeys (11)(12)(13). The plant tuber powder also elicits dose-dependent physiological responses in male mice with a reduction in the weight of the epididymis and the seminal vesicles and reduced sperm motility and viability (14), promoting protection against osteoporosis in orchidectomized male (15) and female rats (16).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that P. candollei var. mirifica (synonym: Pueraria mirifica) possesses pharmacological activity (Chansakaow et al, 2000;Cherdshewasart et al, 2004;Trisomboon et al, 2004;Urasopon et al, 2007 (Bautista et al, 2010) and strains of several Rhizobium and Bradyrhizobium species were isolated from the root nodules of P. candollei var. mirifica (Pongsilp et al, 2010).…”
mentioning
confidence: 99%